Diverse innate immune activation states and cellular cross-talk in the human lung: implications for vaccine strategies and inhalable host-directed therapies - Connolly, Sarah (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2026)
Professional immune cells and structural cells in the lungs collaborate to provide protection against pathogens and pollutants. Complex cross-talk balances inflammatory responses whilst maintaining the integrity of the lung tissue. However, these dynamic interactions can become dysregulated, mediating damage and pathology. Innate immune memory, termed 'trained immunity' reprogrammes myeloid cells towards altered responsiveness to subsequent challenges. Innate memory can result in either heightened inflammatory responses or anti-inflammatory/tolerance-like features. These alternative fates in myeloid cell memory shape pulmonary protection or pathology. The context in which these discreet types of innate memory arise determines the potential for aberrant reactions downstream, exaggerating the prevalence and severity of chronic inflammatory responses, or increasing susceptibility to infection. Lower respiratory tract infections have a major impact on global health, and the COVID-19 pandemic highlighted the importance of vaccination in protecting against severe infection and mortality. Randomised control trials of SARS-CoV-2 vaccines reported lower overall mortality with adenovirus-vector vaccines compared with mRNA vaccines. Therefore, it was hypothesised that altered innate immune responses would be distinct between people vaccinated with these vaccine platforms. Evidence herein showed mRNA-based vaccination demonstrated tolerance-like features associated with downregulated inflammatory responses. In contrast, adenoviral vector-based vaccination increased activation and inflammatory responses, characteristic of proinflammatory trained immunity. Therefore, vaccine platforms drive diverse forms of innate immune reprogramming. Alveolar macrophages (AM) are the sentinels of the human lung which under homeostatic conditions clear debris, pollutants and protect the lung from damage. However, AM also mount effective proinflammatory responses to protect the lung from infection. Findings herein illustrated that the Th1 cytokine IFN-γ primed human AM towards functional plasticity exhibiting an 'M1'-like state to initiate inflammatory responses against bacterial challenges, while the Th2 cytokine IL-4 shifted AM towards a hyporesponsive 'M2'-like state. AM plasticity and function were metabolically controlled and reliant on glycolysis. AM plasticity highlights its potential tractability for therapeutic strategies to strengthen lung immunity. The data presented herein showed IFN-γ induced trained immunity in monocytes heightens responsiveness to secondary challenges. Increased IL-1β and TNF induced by trained immunity amplified proinflammatory responses in human lung structural cells. Enhanced glycolytic metabolism was identified as a key mechanism which mediated this synergistic effect driving inflammation in the innate-structural axis. These trained responses also drove tissue factor and MMP associated with immunothrombosis and tissue destruction, respectively, highlighting the fine balance between protection and damage. These findings suggest that innate memory, inflammatory cross-talk and immunometabolism are key regulatory nodes modulating inflammation in the human lung, with potential tractability for host-directed therapies to promote lung health.
APPROVED
Keywords: Trained immunity; Alveolar macrophage; Epithelial cell; Lung fibroblast; Infection; Monocyte; Host-directed therapies; Vaccines